Rapid Development of Cefiderocol Resistance in Carbapenem-resistant Enterobacter cloacae During Therapy Is Associated With Heterogeneous Mutations in the Catecholate Siderophore Receptor cirA. (3rd June 2021) - Klein, Sabrina; Boutin, Sébastien; Kocer, Kaan; Fiedler, Mascha O; Störzinger, Dominic; Weigand, Markus A; Tan, Benjamin; Richter, Daniel; Rupp, Christian; Mieth, Markus; Mehrabi, Arianeb; Hackert, Thilo; et al.
Abstract: We report a case of resistance development toward cefiderocol in a patient with intra-abdominal and bloodstream infections caused by carbapenemase-producing Enterobacter cloacae within 21 days of cefiderocol therapy. Whole genome sequencing revealed heterogeneous mutations in the cirA gene, encoding a catecholate siderophore receptor, conferring phenotypic resistance to cefiderocol.